Microbiome-mediated neutrophil recruitment via CXCR2 and protection from amebic colitis - Watanabe, Koji (PLoS Pathog, 2017)
The disease severity of Entamoeba histolytica infection ranges from asymptomatic to life-threatening. Recent human and animal data implicate the gut microbiome as a modifier of E. histolytica virulence. Here we have explored the association of the microbiome with susceptibility to amebiasis in infants and in the mouse model of amebic colitis. Dysbiosis occurred symptomatic E. histolytica infection in children, as evidenced by a lower Shannon diversity index of the gut microbiota. To test if dysbiosis was a cause of susceptibility, wild type C57BL/6 mice (which are innately resistant to E. histiolytica infection) were treated with antibiotics prior to cecal challenge with E. histolytica. Compared with untreated mice, antibiotic pre-treated mice had more severe colitis and delayed clearance of E. histolytica. Gut IL-25 and mucus protein Muc2, both shown to provide innate immunity in the mouse model of amebic colitis, were lower in antibiotic pre-treated mice. Moreover, dysbiotic mice had fewer cecal neutrophils and myeloperoxidase activity. Paradoxically, the neutrophil chemoattractant chemokines CXCL1 and CXCL2, as well as IL-1β, were higher in the colon of mice with antibiotic-induced dysbiosis. Neutrophils from antibiotic pre-treated mice had diminished surface expression of the chemokine receptor CXCR2, potentially explaining their inability to migrate to the site of infection. Blockade of CXCR2 increased susceptibility of control non-antibiotic treated mice to amebiasis. In conclusion, dysbiosis increased the severity of amebic colitis due to decreased neutrophil recruitment to the gut, which was due in part to decreased surface expression on neutrophils of CXCR2.